Compound Molecules of Network Pharmacology-Based of Tamarillo (Cyphomandra betacea Cav.) and the Potential as Noodle for Type 2 Diabetes Mellitus Treatment - Fitriyani, Fitriyani; Ningrum, Salsabila E.S.; Mutiah, Rohiatul; Kinasih, Larasati Sekar (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Consuming noodles excessively is not good for health because it contains high trans fat, which can cause diabetes mellitus (DM) as a disease with a high prevalence, especially type 2 DM, as much as 95% in Indonesia. Tamarillo (Chypomandra betacea Cav.) can potentially reduce blood glucose levels and restore adipokine regulation to prevent insulin resistance in type 2 DM. This study aims to determine the formulation and potential of tamarillo compounds into noodle products named